Evaluation of one year immunity following rabies post-exposure prophylaxis in dog bite cases - Nisa Ya; Heidi Auerswald; Sothy Touch; Saraden In; Chanvannak Yun; Pisey Thai; Sotheary Sann; Borita Heng; Chanthy Leng; Veasna Duong; Yik Sing Peng; Sowath Ly; et al. (npj Vaccines, 2024)
Abstract Rabies remains a global health threat despite being preventable with post-exposure prophylaxis (PEP). This study assessed one-year humoral and T cell immunity in PEP recipients of the Insitut Pasteur du Cambodge (IPC) regimen, recommended by WHO. We analyzed rabies virus (RABV) neutralizing antibodies (nAbs) and T cell responses at baseline, 7 and 14 days, 6 and 12 months after PEP. A total of 148 patients were included, with 78 bitten by confirmed RABV-positive dogs receiving PEP and equine rabies immunoglobulins (eRIG), and 70 bitten by RABV-negative dogs receiving only PEP. Fourteen days after PEP, all but two individuals seroconverted for nAbs ( ≥ 0.5 IU/mL) with 87% maintaining this response even after 12 months. Interleukin-4 (IL-4) and interferon-gamma (IFN-γ)-secreting T cells were significantly elevated after 14 days and sustained for one year. No differences were observed between the RABV-exposed and -unexposed groups. This study demonstrates robust one-year immunity after IPC PEP.